Catalytic flexibility of rice glycosyltransferase OsUGT91C1 for the production of palatable steviol glycosides - Jinzhu Zhang (Nature Portfolio, 2021)
Steviol glycosides from the plant Stevia rebaudiana are already used as lowcalorie sweeteners, but the most abundant naturally occurring compounds have a bitter aftertaste. Here, the authors characterize and engineer rice glycosyltransferase OsUGT91C1 to facilitate the large-scale production of naturally rare but palatable glycosides Reb D and Reb M